The Passo Fundo Cohort Study: design of a population-based observational study of women in premenopause, menopausal transition, and postmenopause. Issue 1 (December 2015) - Oppermann, Karen; Colpani, Verônica; Fuchs, Sandra; Spritzer, Poli
Abstract Background The Passo Fundo Cohort Study (PFS) is a population-based longitudinal observational study of pre-, peri-, and postmenopausal women that has been ongoing since 1995 in Passo Fundo, a city in southern Brazil. This paper describes the rationale and design of the PFS and summarizes objectives and procedures that have been updated during follow-up. Methods/Design Women in the PFS have been followed for a variety of diseases that are frequent in menopause. Sampling was conducted in 154 randomly selected census divisions (geographical subdivisions of the city as defined by the Brazilian Institute of Geography and Statistics). One block in each census division was chosen by lot and two women were randomly selected for interview in each block. The first cycle, conducted between 1995 and 1997, included a representative sample of 298 women aged 35 to 55 years. In the second cycle, conducted between 2001 and 2002, additional participants were enrolled based on the same sampling strategy used in 1995, for a final sample of 358 women. In 2010, a third follow-up was initiated, when all 358 participants or their relatives were located. Participants completed a standardized questionnaire on demographic and socioeconomic characteristics. They also answered questions about lifestyle, medical and reproductive characteristics, sexual life, hormone therapy and mental aspects by using validated instruments. Physical activity was assessed and anthropometric measurements, blood sampling and pelvic ultrasound examination were performed. In the third cycle, bone mineral density by dual-energy X-ray absorptiometry and abdominal fat and coronary artery calcium score by computed tomography were also determined. Discussion The study findings provide relevant information to evaluate the association between menopausal status, female aging and the risk of cardiovascular diseases, and bone health aspects in a representative sample of women from southern Brazil.